2020
DOI: 10.1007/s10734-020-00565-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher education contributing to local, national, and global development: new empirical and conceptual insights

Abstract: Higher education offers the potential to support glonacal (global, national, and local) development. This study presents new empirical and conceptual insights into the ways in which higher education can help to achieve and exceed the outcomes enshrined in the Sustainable Development Goals. Open-ended online surveys were used to learn how academics in Georgia and Kazakhstan view the contributions of universities to addressing self-identified development challenges; and how universities work with the government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 31 publications
1
68
0
4
Order By: Relevance
“…Production processes and sensitive delivery are the key to a quality product and this requires dealing with people, while online technological methods make act simply as a process management tool. The product of education remains an ambiguous entity, for example Unterhalter and Howell (2021) argued that graduates are the products of the education system, while Chankselian et al. (2021) explained that knowledge and skills are the products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Production processes and sensitive delivery are the key to a quality product and this requires dealing with people, while online technological methods make act simply as a process management tool. The product of education remains an ambiguous entity, for example Unterhalter and Howell (2021) argued that graduates are the products of the education system, while Chankselian et al. (2021) explained that knowledge and skills are the products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In accordance with the rating of low and high, as indication of level of awareness of available e-learning facilities, the respondents' scores in level of awareness as shown in Table 2, range 1-22 with a mean of 10.9. To find the level of awareness of available e-learning facilities, the scores were grouped into two categories; low (0-11) and high (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The analysis revealed that level of awareness of available e-learning facilities by the respondents, with a majority (71.0%) claiming to be as low, while 29.0% indicated that the level of awareness of available elearning facilities is high.…”
Section: Level Of Awareness Of E-learning Facilities Available To Agricultural Studentsmentioning
confidence: 99%
“…The paradigm of higher education is shifting from the traditional towards an entrepreneurial university, giving different meanings of this term [1][2][3][4]. As the role of academic institutions in stimulating, therefore contributing to, the development of the modern knowledge-based economy has become widely accepted [5], the entrepreneurial university concept in practice has been facilitated by the collaboration between universities, government entities, and industrial partners, as outlined by a triple helix model [6]. So far, the main research has been focused on industry-university relations with respect to technology transfer [7] or university-business cooperation [8].…”
Section: Introduction 1contextmentioning
confidence: 99%